تطبيقات الوظيفة الاستشارية للعلاقات العامة في منشآت القطاع الخاص بالمملكة العربية السعودية - Al-Shibal | الشبل, Muhammad bin Abdul Rahman Youssef | محمد بن عبد الرحمن يوسف (Imam Mohammad Ibn Saud Islamic University | جامعة الإمام محمد بن سعود الإسلامية, 2023)
This questionnaire aims to identify the reality of the applications of the advisory job for public relations in private sector establishments in the Kingdom of Saudi Arabia from A leadership viewpoint: A sample of the 100 largest private sector establishments in the Kingdom (Chairmen of boards of directors, managing directors, general managers, directors executives), especially the advisory functions performed by the management’s public relations upper | تهدف هذه الاستبانة إلى التعرف على واقع تطبيقات الوظيفة الاستشـارية للعلاقات العامة في منشـآت القطـاع الخـاص فـي المملكـة العربيـة السـعودية مـن وجهة نظر قيادي عينة من أكبر 100منشأة من منشآت القطاع الخاص بالمملكـة )رؤساء مجالس الإدارات، الأعضـاء المنتـدبون، المـديرون العـامون، المـديرون التنفيـذيون(، وخاصـة المهـام الاستشـارية التـي تؤديهـا العلاقـات العامـة لـلإدارة العليا